The personal nature of individual criminal responsibility and the ICC Statute - Militello, Vincenzo (Journal of international criminal justice, 2007)
By affirming criminal responsibility of the individual, the ICC Statute recognizes a distinction from the international responsibility of states, which is the basis of modern international criminal law. The importance of the principle is evident not only in the breadth and analytical nature of the provision dealing with it, i.e. Article 25 of the Statute, but by its being placed in the part of the Statute devoted to the General Principles of Criminal Law . After an introductory consideration of the context of the Article and of its general implications, this article analyses the contents of the regulation and the type of responsibility outlined in it. The principle that emerges could be called the personal nature of international criminal responsibility. Although the general principles set out in the ICC Statute are rather rudimentary in comparison with what is to be found in the General Part of most national criminal laws, the principle of personal responsibility emerging from the Statute is nevertheless in the best traditions of criminal law. It serves both as the foundation and as the limitation of international criminal responsibility, so helping to ensure that modern international criminal law is not a tool for oppression but rather an instrument of justice